2009
DOI: 10.4103/0019-509x.55551
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-based chemotherapy: Add high-frequency audiometry in the regimen

Abstract: As use of high-frequency audiometry is still limited in research work only, we need a strict protocol of adding high-frequency audiometry in the cisplatin-based chemotherapy regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 21 publications
3
20
0
1
Order By: Relevance
“…Similarly, Kopelman et al (1988) [13] reported that 100% of their patients with advanced cancers showed some degree of hearing loss, while Nagy et al (1999) [14] revealed that 36% of the 53 patients with oesophageal, lung or head and neck cancer presented with cisplatin-associated ototoxicity. Data from India also revealed similar findings [4, 10]. Whitehorn et al (2014) [11] reported that 55.1% of the patients in their retrospective study developed ototoxicity while receiving high-dose (≥60 mg/m2) cisplatin treatment.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Similarly, Kopelman et al (1988) [13] reported that 100% of their patients with advanced cancers showed some degree of hearing loss, while Nagy et al (1999) [14] revealed that 36% of the 53 patients with oesophageal, lung or head and neck cancer presented with cisplatin-associated ototoxicity. Data from India also revealed similar findings [4, 10]. Whitehorn et al (2014) [11] reported that 55.1% of the patients in their retrospective study developed ototoxicity while receiving high-dose (≥60 mg/m2) cisplatin treatment.…”
Section: Introductionmentioning
confidence: 57%
“…However, while cisplatin chemotherapy is the treatment modality in advanced carcinogenesis, the resulting toxicity profile from the use of such regimens is expansive and affects the gastrointestinal, haematologic, renal and auditory systems [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in the 1970s [7], cisplatin continues to be hailed as one of the most potent cancer chemotherapeutics in children and adults, as it is unique and unmatched in its effectiveness against many cancers [4], namely, osteogenic sarcoma, medulloblastoma, testicular, cervical, and ovarian cancers [8]. Similarly, its toxicity profile is expansive, involving the gastrointestinal, hematologic, renal, and auditory systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, its toxicity profile is expansive, involving the gastrointestinal, hematologic, renal, and auditory systems [8]. While the use of saline hydration and mannitol diuresis may prevent nephrotoxicity, neurotoxicity is still not curable or preventable [9].…”
Section: Introductionmentioning
confidence: 99%
“…This damage occurs in a relatively orderly manner of base (high frequency) to apex (low frequency) destruction [10] primarily of the outer hair cells, which are sensory receptor cells that provide for the large dynamic range and exacting frequency selectivity that characterizes human hearing. Damage also occurs to the marginal cells of the stria vascularis [11][12][13][14], which provides the electrochemical drive for the outer hair cells and spiral ganglion cells of the auditory nerve.…”
Section: Introductionmentioning
confidence: 99%